Religião e Movimento Social: as representações religiosas dos pentecostais do Assentamento Herbert de Souza, Moreno, Pernambuco - Ferreira, Fábio Alves (2008)
This research aims to describe and analyze the religious representations of the Pentecostals from Herbert de Souza Settlement, located in Moreno in Pernambuco state. In the course of the investigation, we noticed that the Pentecostal settlers, all of them beneficiary from the Movement of the Landless Rural Workers (MST), update their religious representations in accordance with the demands of life that led them to enter upon land that belonged to Engenho Pinto. It was also observed that the place and time in which happened the entry of each Pentecostal caused them to build up different religious interpretations about the movement, land, and about what they understand by religious practice. Therefore, they make up symbolic meaning networks that organize their world conceptions. We compared the representations of the Pentecostals who already lived on the land before the occupation of Engenho, to those of the ones who came afterwards, already as MST activists, or that simply gained any benefit from the process of land democratization. We created three ideas about the Pentecostals: the pre-occupational group, the post-occupational and pro-occupational ones. Finally, we considered that their representations are developed in times of crisis in which there is an compromise between the speech of MST and what is systematized in the church doctrines to which the believers are attached. Therefore, juncture is essential to the emergence of a process of negotiation between the Pentecostals doctrinaire practices and the requirements of MST.(AU)